Ministrantura w posoborowej pedagogii Franciszka Blachnickiego (wprowadzenie do problemu) - Sadowska, Katarzyna (Biuletyn Historii Wychowania, 2021)
The aim of the study is to present the formation of altar boys in the post-conciliar pedagogical teaching of priest Franciszek Blachnicki, an outstanding mystagogue of the Second Vatican Council, in the context of Christian education. The post-conciliar documents changed the severity of the Church, pompous and inaccessible to laymen. Concern for the community of the faithful became the dominant idea of the Second Vatican Council. In connection with the changes taking place in the Church and the needs of Catholics in the Polish People’s Republic, Franciszek Blachnicki made an attempt to lay the foundations for pastoral theology. It included the metho-dological assumptions underlying Catholic communities, placed by the priest in the philosophy of the Christocentric tradition, and based on a dialogue derived from “a philosophical meeting”, mutual service and the value of spiritual experience. The work of Franciszek Blachnicki, which remains valid, has made its way to the history of the Polish Catholic Church. While the priest is widely recognized as the founder of the Light – Life movement, he built the foundations for the concept of work for “communion” when altar service was the only communion approved by the Polish Church authorities.